A Pilot Retrospective Study of the Relationship Between Estrogen Use and Pancreatitis/Pancreatic Function in Women with Chronic Abdominal Pain - Lieb II, John George; Toskes, Phillip P (JOP. Journal of the Pancreas, 2013)
Context Estrogens are thought to cause pancreatitis by raising triglyceride levels but whether there are other effects on the pancreas is debatable. Objective To better elucidate the relationship between estrogens and pancreatitis and pancreatic function in a pilot study. Design/setting/patients Our retrospectively collected database of 224 patients who had undergone secretin stimulation testing was queried for females with available medication histories, who were then divided into two groups: those taking estrogens (E) and those not on estrogens (N). Mann Whitney U and Fisher’s exact tests were used. Results Seventy of the patients in the database were females with available medication histories. Thirty-five (50.0%) were taking estrogens. Twenty-nine (82.9%) of the E patients experienced any type of pancreatitis (i.e., acute pancreatitis, acute relapsing pancreatitis, chronic pancreatitis) while only 19 (54.3%) of the N patients did (P=0.019). During secretin stimulation testing, the peak bicarbonate levels for E and N patients were 80±18 and 90±23 mEq/L, respectively (P=0.058). When patients with any type of pancreatitis were excluded, E patients still displayed decreased peak bicarbonate levels in response to secretin (90±18 vs. 104±19 mEq/L; P=0.021). Weight, age, triglyceride levels, frequency of patients with cholecystectomy and biliary stones did not significantly differ between the two groups (E and N respectively). Conclusions These pilot data suggest exogenous estrogens may be related to the development of acute pancreatitis and acute relapsing pancreatitis, and probably to a lesser degree chronic pancreatitis, perhaps through a triglyceride independent mechanism. During secretin stimulation testing, peak bicarbonate production may be diminished in women on estrogens (even in those who have never had pancreatitis). Further study is necessary to better define the relationship between estrogen use, pancreatitis, and pancreatic function. Image: Pancreatic function by peak bicarbonate.